HFS‐Triggered AMPK Activation Phosphorylates GSK3β and Induces E‐LTP in Rat Hippocampus In Vivo. (25th March 2016) - Yu, Dan‐Fang; Shen, Zu‐Cheng; Wu, Peng‐Fei; Guan, Xin‐Lei; Chen, Tao; Jin, You; Hu, Zhuang‐Li; Ni, Lan; Wang, Fang; Chen, Jian‐Guo; Long, Li‐Hong
Summary: Background: The AMP‐activated protein kinase (AMPK) is a sensor of cellular energy and nutrient status, with substantial amount of cross talk with other signaling pathways, including its phosphorylation by Akt, PKA, and GSK3 β . Aims: Various signaling pathways and energy‐consuming transport of glutamate receptors subunits are required in synaptic plasticity. However, it is unknown which energy sensors integrate the signaling pathways in these processes. In this article, we elucidated the role of AMPK activation and GSK3 β phosphorylation after HFS during the inducement of early‐phase long‐term potentiation (E‐LTP). Methods: Synaptic LTP in vivo was induced by high‐frequency stimulation (HFS at 200 Hz at a 5‐s interval). In addition, phosphorylation of AMPK and glycogen synthase kinase 3 β (GSK3 β ) were measured using Western blotting. The amount of hippocampal AMP, ADP and ATP was measured by HPLC. Results: We showed that the phosphorylation of AMPK and GSK3 β was significantly increased by HFS in vivo . HFS‐induced AMPK activation occurred via increased (AMP + ADP)/ATP ratio and activation of Ca 2+ /calmodulin‐dependent kinase kinase beta (CaMKK β ). Pharmacological inhibition of AMPK by compound C (CC) prevented HFS‐induced inhibitory phosphorylation of GSK3 β and the induction of LTP in dentate gyrus (DG) area in vivo . Conclusions: Our findings reveal that HFS‐triggered AMPK activation phosphorylates GSK3 β and induces E‐LTP in vivo .